Financial structure and earnings manipulation activities in China. (30th November 2021) - Khan, Muhammad Kaleem; Qin, Yixuan; Zhang, Chengsi
Abstract: This study aimed to analyse the monitoring adeptness of the financial system in China, particularly in controlling earnings management activities. First, this study identifies the reasons and motivations of managers for involvement in earnings management activities. Second, this study determines whether China's financial system has developed sufficiently to be capable of establishing a strong monitoring mechanism over firms. The study compares how an equity‐based financial structure develops an efficient monitoring system with that of a bank‐based one. A panel dataset of 2997 listed Chinese firms spanning the years 1998–2015 shows that the agency issue is the main reason that firms engage in earnings management activities. Management of financially constrained firms is found to be more prudent than management of other firms because they avoid masking firm performance. The study concludes that Chinese firms are restrained from indulging in managing earnings practices owing to the overwhelming development of the financial system. Moreover, firms in capital market‐based financial structures are more inclined to avoid earnings management compared with those in bank‐based structures.